Optimización en los procesos de participación al Programa Techo Propio, Empresa NORDIKA SAC - período 2011-2021 - Velásquez Santisteban, Ezequiel Marco Antonio (2023)
This report is to opt for the title of Bachelor of Administration, entitled "Proposal for optimization in the processes of participation in the Techo Propio program, company Nordika SAC period 2011-2021", its general objective is to design a proposal for optimization in the processes of participation in the own roof program in the company Nordika SAC, this being a contribution to the company in the administrative field in order to present the proposal and design a manual of procedures to apply the functions determined in it, as well as apply the management instruments and business policies for productivity, quality and performance control established in the Organization and Functions Manual (MOF), Procedures Manual, Business Policies and Strategic Plan of Strengths and Weaknesses. It is concluded that for the recruitment of office personnel and recruiters in areas outside of Trujillo it is necessary to implement a human resources area where each evaluation process is carried out by professionals specialized in the subject, working as a team with the Financial and Administrative Management; In order to increase the company's capacity to meet the demand for applications for registration to the Techo Propio program, a diagnosis of demand attention, an improvement plan, a calculation of productivity and cost must also be carried out. -Benefit, to carry out periodic evaluations and prevent the problem from recurring, thus optimizing the processes of participation in the company's own roof program.